How Bats Escape the Competitive Exclusion Principle—Seasonal Shift From Intraspecific to Interspecific Competition Drives Space Use in a Bat Ensemble - Roeleke, Manuel; Johannsen, Lilith; Voigt, Christian C. (Frontiers in Ecology and Evolution, 2018)
Finding prey is crucial for predators that hunt on patchily distributed prey aggregations. At prey-rich patches, intraspecific and interspecific competition should be high. While the competitive exclusion principle suggests that species can only coexist if their ecological niches show considerable differences, newer theory suggests stabilizing and equalizing mechanisms besides classical niche differences that facilitate local coexistence. To identify such mechanisms, the understanding of the strength and nature (i.e. interference or exploitation) of competition in a species ensemble is a prerequisite. Here, we investigated intra- and interspecific competition between aerial-hawking insectivores, using the interactions between two open-space foraging bats as a model. In particular, we tested for shifts in space use of the common noctule bat Nyctalus noctula in response to simulated aggregations of conspecific and heterospecific competitors at foraging patches. When confronted with playbacks of heterospecific Pipistrellus nathusii, N. noctula increased their activity in the experimental area in early summer, but decreased activity in late summer. When confronted with playbacks of conspecifics, activity of N. noctula remained the same, irrespective of season. This pattern was accompanied by a decrease in the proportion of large insects during late summer. Our results suggest that intraspecific competition is more severe than interspecific competition for aerial insectivores in early summer. Probably, conspecifics engage in interference competition for flight space, and in the case of echolocating bats, may interfere with each other’s echolocation calls. Interspecific competition may be mediated by fine scale vertical partitioning and the use of different, non-interfering echolocation frequencies during insect rich times. In contrast, during late summer, bats may rather compete for the exploitation of relatively scarce large prey items. We speculate that N. noctula decreased activity in response to P. nathusii playbacks due to its inferior manoeuvrability and thus probably inferior hunting success in the presence of smaller, more agile bat species. However, N. noctula’s specialization on fast and efficient flight may enable them to use farther away and possibly less rich foraging patches, thus equalizing for a lower fitness compared to superior hunters.